(3eLjH GdfOG Edi TQM bWQ GdfOGs - (3GdaGcgj Gdecj, LeGd GdOjf, YHO Gddg Hf CMeO Hf YHO Gddg Hf CMeO Hf Ydj, (B972 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdQGaY ef GfNaV dYRg hSdWGfg(B...(3CeG HYO agPG TQM dWja hVYJg Ydi(B...(3GdeSeGI HbWQ GdfOi hHd GdUOi(B...s
(3BNQgG (B:s
(3hdjcf gPG BNQ eG CQOfG EjQGOg Ydi gPg GdebOeI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B69s
(3cTa GdXfhf(B:(3L(B2(3,U(B1352s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs